ANALISA BULLWHIP EFFECT PENGADAAN STOCK FRANCHISE AYAM SABANA - ADE IRPAN SABILAH (Universitas Putera Batam, 2021)
The COVID-19 pandemic made some companies must pay attention to all their business needs appropriately and measurably. Strategic use in some companies there is making the limited on the stock supply, it is expected to reduce the losses that will be experienced by business people. The Sabana franchise has problems in determining the optimal safety stock so that there is no bullwhip effect in the supply chain for these raw materials. The purpose of this study is to determine the value, causes, and proposed solutions to reduce the occurrence of the Bullwhip Effect and can optimally forecast inventory requirements using the Single Exponential Smoothing method. The results obtained from this study are the magnitude of the bullwhip effect that occurs in the supply chain Franchise Sabana, which has a value of 1.036 and the value is greater than 1. which means that there has been a Bullwhip effect on the observed supply chain. From the analysis results, it is known that the causes of the Bullwhip effect include the absence of system users and strategies in forecasting needs, unmeasured supply or inventory shortages, fluctuating price fluctuations, order sizes, and order fulfillment grace periods, and forecasting results for inventory in the next month. of 663.6 kg with a minimum stock limit of 351.7 kg and a maximum stock limit of 975.6 kg. Ways that may be effective to reduce the bullwhip effect that occurs include managing product availability properly, namely by applying forecasting on controlled sales of raw material orders and also the accuracy of information from product sales so that business owners will find it easy to calculate forecasting values for the period to come. come to be able to optimally and efficiently in financing business activities.